Academic learning in law : theoretical positions, teaching experiments and learning experiences - Klink, Bart van; Vries, U. R. M. Th. de. (Cheltenham, UK : Edward Elgar Publishing Limited, 2016)
The nature and purpose of legal education has become a topic of intense debate in recent years. This timely book calls for a critical re-evaluation of university legal education, with the particular aim of strengthening its academic nature. The contributors emphasize lecturers' responsibility to challenge the assumptions students have about law, and the importance of putting law in a theoretical and social context that allows for critical reflection and sceptical detachment. In addition, the book reports upon teaching experiences and innovations, offering tools for teachers to strengthen the academic nature of legal education, and concludes with concrete proposals for change. Students and scholars engaged in the debate regarding the re-evaluation of academic legal education will find this book invaluable to their work. It will also be of interest to practitioners, such as educational experts and administrators looking to understand the role of law schools in creating responsible citizens.
1. Introduction -- PART I. THEORY AND LEGAL EDUCATION -- 2. Knowledge and aphasia : what is the use of skeptical legal education / Bart van Klink -- 3. Re-bildung : an ideal reconsidered for legal education / Lyana Francot and Luigi Corrias -- 4. Academic education and socialisation / Anja Boning -- 5. The necessary loneliness of teaching / Anthony Bradney -- PART II. EXPERIMENTAL COURSES -- 6. Teaching international law critically / Christine Schwobel-Patel -- 7. Learning law differently : the importance of theory and methodology / Bal Sokhi-Bulley -- 8. Empirical methodologies knowledge and expertise : a'necessary' skill for lawyers? / Terry Hutchinson -- 9. Using visuals for a critical reflection on law / Wibo van Rossum -- 10. For a new and more diverse comparative legal education / Sabrina Germain -- PART III. DIDACTIC INNOVATIONS AND LEARNING EXPERIMENTS -- 11. Orchestrating encounters / Barbara Oomen -- 12. Ethical awareness and legal education / Gulriz Uygur -- 13. Learning how to read a case : resources from the visual and dramatic art / Maksymilian Del Mar -- 14. Law & lounge : an experiment about student self-organisation and critique as skeptical reflexivity / Ubaldus De Vries -- 15. Epilogue : an overview, reflections and a student's perspective / Tim Bleeker
Includes bibliographical references and index.
Keywords: Law -- study and teaching